Virginia Hamilton : America's Storyteller - Rubini, Julie (Book collections on Project MUSE., 2017)
"In Virginia Hamilton, Julie K. Rubini brings us the biography of one of the most honored authors of children's literature in the twentieth century. The most expansive biography of Hamilton published for young readers, it was vetted for accuracy by Hamilton's husband, poet Arnold Adoff. It is the fourth installment in the Biographies for Young Readers series, which is quickly building a reputation for substantive and engaging treatments of its diverse subjects. Long before she wrote The House of Dies Drear, M. C. Higgins, the Great, and many other modern classics, Hamilton grew up among her extended family around Yellow Springs, Ohio. The stories she heard from her family fueled her imagination, and the freedom to roam the farms and woods nearby sharpened her powers of observation and encouraged her creativity. As she grew older, witnessing racial discrimination and the response of the early civil rights movement established in her a lifelong commitment to representing a diversity of experiences in her work. In all, Virginia wrote forty-one books, which are driven by her focus on "the known, the remembered, and the imagined"-- particularly within the lives of African Americans. Hamilton's middle-grade readership will delight in the mix of historical detail, childhood recollections, photos, and quotations that Rubini draws on to bring Hamilton's story to life"--